Design and Architecture for the Dawn of the personal Computer. The pioneer vision of Adriano Olivetti - Rocha, João (2017)
In 1952 the Italian Olivetti Company opened a study laboratory on electronic calculators in New Canaan, USA; in 1955 it created an electronic research laboratory in Pisa and two years later, co-founded a company to produce electronic conductors. In 1959 it presented ELEA 9003 and in 1965 the P101, respectively the first full transistorized computer and the first desktop computer. This paper aims to investigate how the Olivetti Company accomplished in such a brief period of time a pioneer vision in the field of computing. By one hand it seeks to highlight the forerunner idea of Adriano Olivetti (1901-1960) for an integrated awareness of what computing could become and on the other hand, how that wakefulness fostered an innovative agenda among architects, designers, filmmakers and scientists for the invention of the computer as an artifact expression of an epoch. This successful endeavor anticipated what would become the concept of personal computing. Moreover the paper underlines how the early commercial development of Olivetti and IBM computing flourished in the context of the Universal Exhibitions of Brussels and New York.